Deficiency of the intermediate filament synemin reduces bone mass in vivo - Moorer, Megan C. (Am J Physiol Cell Physiol, 2016)
While the type IV intermediate filament protein, synemin, has been shown to play a role in striated muscle and neuronal tissue, its presence and function have not been described in skeletal tissue. Here, we report that genetic ablation of synemin in 14-wk-old male mice results in osteopenia that includes a more than 2-fold reduction in the trabecular bone fraction in the distal femur and a reduction in the cross-sectional area at the femoral middiaphysis due to an attendant reduction in both the periosteal and endosteal perimeter. Analysis of serum markers of bone formation and static histomorphometry revealed a statistically significant defect in osteoblast activity and osteoblast number in vivo. Interestingly, primary osteoblasts isolated from synemin-null mice demonstrate markedly enhanced osteogenic capacity with a concomitant reduction in cyclin D1 mRNA expression, which may explain the loss of osteoblast number observed in vivo. In total, these data suggest an important, previously unknown role for synemin in bone physiology.